Faktor yang Mempengaruhi Preferensi Masyarakat pada Pelayananan Kesehatan RSU Mitra Sejati Medan Johor - Ivany Vatriscia (Jurnal Health Sains, 2021)
The hospital has a mission to provide quality health services. Good service quality will affect people's preferences which in turn will affect consumers in choosing the services provided. This research aims to analyze the factors that influence people's preferences for health services at Mitra Sejati Hospital in Medan Johor District. The type of research used in this research is an analytic survey with a cross sectional study design, which is conducted on people who have been treated at Mitra Sejati Hospital as a patient in 2020 with a sample of 93 people taken using accidental sampling technique. The results of the study, there is no relationship between work, education, ownership of health insurance to people's preferences but there is a relationship between income and community preferences. The conclusion obtained from the results of this study is that the people of Medan Johor district mostly have moderate education, work as private workers, have incomes that are not in accordance with MSEs and the preferences of people who do not choose the hospital health service anymore. There is no link between employment, education, ownership of health insurance to people's preferences. There is a link between income and people's preferences.